Key molecular DNA damage responses of human cells to radiation - Zhang, Chencheng; Liu, Jibin; Wu, Jun; Ranjan, Kamakshi; Cui, Xiaopeng; Wang, Xingdan; Zhang, Dianzheng; Zhu, Shudong (Frontiers in Cell and Developmental Biology, 2024)
Our understanding of the DNA damage responses of human cells to radiation has increased remarkably over the recent years although some notable signaling events remain to be discovered. Here we provide a brief account of the key molecular events of the responses to reflect the current understanding of the key underlying mechanisms involved.